2019
DOI: 10.15694/mep.2019.000214.1
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative mentoring for effective medical research groups

Abstract: Research benefits professors and students, mentors and mentees, however, many Universities lack formal programs, especially in basic sciences such as anatomy. Faculty, many times, lack the time, resources, and a well-structured program. Mentoring and collaborative work, have played an important role in creating an effective environment that inspires its members into scientific production, enhances research skills, while gaining experience. The authors presented a student anatomy research group (Grupo de Invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The results from this study suggest an effective strategy for student research recruitment would begin by including the professors and students (peers) already involved, to inspire and motivate through example. A motivating strategy has been shown to be more successful (Reyes-Hernández et al, 2016;Elizondo-Omaña et al, 2019), and forced participation has been poorly received (Pololi and Knight, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study suggest an effective strategy for student research recruitment would begin by including the professors and students (peers) already involved, to inspire and motivate through example. A motivating strategy has been shown to be more successful (Reyes-Hernández et al, 2016;Elizondo-Omaña et al, 2019), and forced participation has been poorly received (Pololi and Knight, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Having these types of interactions is much less likely for the participants in loosely structured research groups (Feldman et al, 2013). In Ivette's case, however, the tightly organized and well-structured research group model that had collaborative mentoring increased training, experience, and scientific output (Elizondo-Omaña et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Valente (2018) found that research groups that have characteristics similar to ones that are tightly organized provide support for participants to improve their understandings of the nature of science. Similarly, Elizondo-Omaña et al (2019) found that well-structured, formal research groups that integrate faculty from different fields through a collaborative mentoring model increases training, experience, and scientific output. Kobulnicky and Dale's (2016) community mentoring model has similarities with the tightly structured research groups.…”
Section: Structure Of Research Groupsmentioning
confidence: 94%
“…Other well-established research groups within the University had promoted student involvement with established authorship and collaborative mentoring to create young researchers [ 39 ]. The anatomy research group (GIA [ Grupo de Investigación en Anatomía ]) established in 2003, has a well-structured program that mentors undergraduate medical students in educational research and anatomical research with clinical orientation, with authorship in their scientific production.…”
Section: Creating Researchers – Uanl Strategiesmentioning
confidence: 99%
“…It also implemented a contact database (Affinity Invest) for researchers and students with similar interests to communicate and collaborate. Although student involvement continues to be low (2.5%) due to a very large student volume (>7500 students enrolled in the 6-year program), the majority of those involved (60%) have established authorship in a published paper [ 22 , 39 ].…”
Section: Creating Researchers – Uanl Strategiesmentioning
confidence: 99%